Lymph node dissection in the surgical management of atypical endometrial hyperplasia - Whyte, Jill S.; Gurney, Elizabeth P.; Curtin, John P.; Blank, Stephanie V. (American journal of obstetrics and gynecology, 2010)
The aim of this study was to evaluate the effect of lymph node dissection in patients with atypical endometrial hyperplasia. Patients undergoing surgical management of atypical endometrial hyperplasia during the study period were retrospectively identified. Clinical and pathologic information was analyzed. Eighty-eight patients comprised our cohort. Median age was 54 years (range, 37–85 years). Sixty-seven patients had lymph node dissection at the time of surgery for atypical endometrial hyperplasia, whereas 21 did not. Twenty-five of 88 (28.4%) had endometrial carcinoma on final uterine pathology. Stages were as follows: 4 IA, 15 IB, 3 IC, 2 IIB, and 1 IIIC. Surgical outcomes were not statistically significant between staged and unstaged groups. Information from lymph node dissection influenced management decisions in 7 of the 25 (28%) cancer patients. Lymph node dissection did not adversely affect surgical outcomes in patients with atypical endometrial hyperplasia. Because many of these patients have concurrent endometrial cancer, we recommend consideration of lymph node dissection in atypical endometrial hyperplasia patients undergoing definitive surgical treatment.